Strengthening the Pancasila Student Profile Project to Develop Student Innovation and Creativity - Yumarna, Yumarna; Kusumawati, Yayuk; Fuaddudin, Fuaddudin (Yayasan Indonesia Emerging Literacy Education, 2025)
Education in Indonesia is faced with the challenge of developing 21st-century skills in students, such as creativity, innovation, and collaboration, which are needed to face rapid global changes. To that end, the Pancasila Student Profile Program (P5) was introduced as one of the educational approaches that focuses on strengthening students' character and skills. This study aims to explore and analyze the role of P5 in strengthening the development of students' innovation and creativity in Indonesian schools. The main focus of the study is to understand how P5 contributes to the formation of students' critical thinking, creativity, and collaboration skills in facing future challenges, while still being based on Pancasila values. This study uses a descriptive qualitative approach with a case study method, involving in-depth interviews with teachers, students, and principals, as well as direct observation in the classroom. The collected data were analyzed using a thematic analysis approach to identify patterns related to the development of students' character and skills through the implementation of P5. The results of the study indicate that P5 not only strengthens students' innovation and creativity abilities, but also improves their collaboration and critical thinking skills, which are very important in facing global challenges. The significance of this research lies in its contribution to understanding how Pancasila value-based education can develop 21st century skills in Indonesia.